After the Before Times - Barrett, Sarah E. | https://orcid.org/0000-0003-3454-9467 (Open Book Publishers, 2026)
In March 2020, when schools across Ontario, Canada closed and emergency remote teaching and learning (ERTL) began, 160,000 teachers were abruptly separated from their students and from the relational fabric that sustains classroom life. After the Before Times documents how teachers experienced those early months of COVID-19 pandemic pedagogy—and what their stories reveal about the nature of teaching and learning.Drawing on interviews with ﬁfty primary and secondary school teachers, Sarah Barrett moves beyond questions of technology and technique to explore relationships: with government, school boards, colleagues, parents, students, and self. In the ‘negative space’ of pandemic pedagogy, teachers identiﬁed what was hardest to replicate at a distance: trust, community, professional integrity, and care.Grounded in the African philosophy of Ubuntu, ‘I am because we are’, this book offers a timely reflection on crisis, integrity, and the relational foundations of a good quality education.